Dependence of charge carrier injection on the interface energy barrier in short-channel polymeric field effect transistors - COEY, JOHN; STAMENOV, PLAMEN (My University, 2012)
The influence of contact materials on the electrical characteristics of field-effect transistors made from poly(3-hexylthiophene) with short-channel lengths of 80nm is investigated. The thermally activated output current indicates the presence of a potential barrier at the electrode/organic contact. The barrier is not related to surface oxide and results in non-linear junction characteristics with activation voltage that can be only partially controlled via the work function of the contact metal. A Schottky contact at the metal/polymer interface arises from the band offset of the two materials and from interfacial dipole layers. Transistor operation with on/off ratio over 10 3 is achieved with five different electrode materials
PUBLISHED
Keywords: Gold; Organic semiconductors